Digestible indispensable amino acid score (DIAAS): 10 years on - Moughan, Paul J.; Lim, Wen Xin Janice (Frontiers in Nutrition, 2024)
The objective of the review is to revisit the findings of the 2011 Food and Agriculture Organization of the United Nations (FAO) Expert Consultation on Dietary Protein Quality Evaluation in Human Nutrition, and to report on progress on uptake of the findings. It is evident that since 2011 there has been a concerted research effort to enhance an understanding of the protein quality of foods. The validity of the growing pig ileal protein digestibility assay has been confirmed and numerous studies reported using the growing pig as a model to give true ileal amino acid digestibility values for foods as consumed by humans. This has allowed for the determination of digestible indispensable amino acid scores (DIAAS) for a range of foods. A new non-invasive true ileal amino acid digestibility assay in humans which can be applied in different physiological states, called the dual-isotope assay, has been developed and applied to determine the DIAAS values of foods. It is concluded that DIAAS is currently the most accurate score for routinely assessing the protein quality rating of single source proteins. In the future, the accuracy of DIAAS can be enhanced by improved information on: the ideal dietary amino acid balance including the ideal dispensable to indispensable amino acid ratio; dietary indispensable amino acid requirements; effects of processing on ileal amino acid digestibility and lysine bioavailability. There is a need to develop rapid, inexpensive in vitro digestibility assays. Conceptual issues relating DIAAS to food regulatory claims, and to holistic indices of food nutritional and health status are discussed. The first recommendation of the 2011 Consultation regarding treating each indispensable amino acid as an individual nutrient has received little attention. Consideration should be given to providing food label information on the digestible contents of specific indispensable amino acids.